Clinical features of supranuclear palsy - T. A. Valikova; V. M. Alifirova; N. V. Pugachenko; R. B. Tsyrenzhapova; A. B. Bichik (Бюллетень сибирской медицины)
Progressive supranuclear palsy related to neurodegenerative diseases of the brain. In the pathological process involved, and stem structure. The disease manifests a combination of progressive akinetic-rigid syndrome and early development of postural instability leading to frequent falling. Observed supranuclear ophthalmoplegia, pseudobulbar syndrome and dementia of frontal. Arises at the age of 50—60, rapidly progressive, and untreatable protivoparkinsonicheskimi drugs. An clinical case of a patient 59 years old, with these magnetic resonance imaging of the brain.